Strategic direction of state assistance to enterprises development in Ukraine: managerial and financial aspects - Zahorskyi, V.; Lipensev, A.; Mazii, N.; Bashtannyk, V.; Akimov, O. (My University, 2020)
The article substantiates the strategic directions of state assistance to the development of enterprises in Ukraine, i.e. managerial and financial aspects. It proves that the sphere of entrepreneurship, like any other social activity, is subjected to the influence of the regulatory policy of the state. We have also stated that business units carry out self-regulation of their operation, which is adjusted by the objective laws of the market mechanism, within which all entities in the society function. It has been argued that the assistance of the state is just to regulate and support the development of enterprises through the activities of public authorities of central, regional and local levels. We would like to note that in developed countries the state plays a significant role in the process of managing small and medium-sized enterprises, which today in the EU are more than 80 % of the total number of economic entities. We emphasize that the primary goal of the state policy of the European countries is to balance the interests of the state and business, to provide optimal conditions for entrepreneurial activity, to increase the competitiveness of the business. In particular, this policy is implemented through the actions of states and special programs performed under the auspices of the European Union. Business support measures are funded through EU structural funds such as the Regional Development Fund and the Social Fund. The data of the influential international research «The Global Competitiveness Report» of the World Economic Forum in 2019 is given, according to which the highest place in the ranking is the indicator «Cost of starting a business» – Ukraine ranks 14th among 141 countries. We would like to note that other indicators that determine the managerial role of the state, such as administrative costs and regulatory framework, are in the second half of the rating. It is found that obstacles to the active development of entrepreneurship in Ukraine are because of the following problems: the lack of proper financing; information vacuum; less diversification of the business environment; in many cases, the absence of an «airbag» for business development; independent lending by entrepreneurs to their clients, resulting in cash gaps; high level of corruption; lack of proper education, which is the main reason for the bankruptcy of many newcomers in the early years; the problem of scaling business with experienced entrepreneurs; business model crisis and difficulties in conquering new markets; personnel crisis in Ukraine and especially in the regions. It is noted that the efficiency of investments of enterprises is significantly improved due to the implementation of innovative projects. We have stated that the innovative vector of state assistance to the development of enterprises should provide for the implementation of both the general state strategy, which will take into account the introduction of innovations into the economic activity of the entities and also the innovative approach of specific enterprises, development by them of projects for the creation of innovative products. Innovation can increase the competitiveness of business entities on the market by improving the management of enterprises, quality marketing, personnel and innovation policies.

Обґрунтовано стратегічні напрями державного сприяння розвиткові підприємств в Україні, а саме управлінських та фінансових аспектів. Доведено, що сфера підприємництва, як і будь-яка інша суспільна діяльність, піддається впливу регуляторної політики держави. Зазначено, що одиниці господарювання здійснюють саморегулювання своєї діяльності, яке коригується об’єктивними законами ринкового механізму, в межах якого функціонують усі суб’єкти в суспільстві. Стверджено, що сприяння держави полягає у регулюванні та підтримці розвитку підприємств через діяльність органів публічної влади центрального, регіонального і місцевого рівнів. Зазначено, що в розвинутих країнах держава відіграє значну роль у процесі управління малими і середніми підприємствами, яких на сьогодні в ЄС більше ніж 80 % від загальної кількості суб’єктів господарювання. Виокремлено, що головною метою державної політики європейських країн є збалансування інтересів держави і бізнесу, забезпечення оптимальних умов для підприємницької діяльності, збільшення конкурентоспроможності бізнесу. Зокрема, ця політика здійснюється через діяльність держав і через спеціальні програми, які реалізуються під егідою Євросоюзу. Фінансування заходів із підтримки бізнесу здійснюється із структурних фондів Євросоюзу, таких як Фонд регіонального розвитку, Соціальний фонд. Наведено дані впливового міжнародного дослідження «The Global Competitiveness Report» Всесвітнього економічного форуму 2019 року, відповідно до яких найвище місце в рейтингу займає показник «Вартість відкриття бізнесу» — Україна перебуває на 14-му місці серед 141-ї країни. Зазначено, що інші показники, які визначають управлінську роль держави, такі як адміністративні витрати і нормативна база, перебувають у другій половині рейтингу. З’ясовано, що на перешкоді активному розвиткові підприємництва в Україні стоять проблеми, зокрема: брак належного фінансування; інформаційний вакуум; менша диверсифікація підприємницького середовища; відсутність у багатьох випадках «подушки безпеки» для розвитку бізнесу; самостійне кредитування підприємцями власних клієнтів, унаслідок чого відбуваються касові розриви; високий рівень корупції; брак відповідної освіти, що є основною причиною банкрутства багатьох новачків у перші роки діяльності; проблема масштабування бізнесу в досвідчених підприємців; криза бізнес-моделі та труднощі із завоюваннями нових ринків; криза кадрів в Україні й особливо в регіонах. Зауважено, що ефективність інвестицій підприємств суттєво підвищується внаслідок реалізації інноваційних проєктів. Зазначено, що інноваційний вектор державного сприяння розвиткові підприємств повинен передбачати реалізацію як загальної стратегії держави, що враховуватиме впровадження інновацій у господарську діяльність суб’єктів, так і інноваційних стратегій конкретних підприємств, розроблення ними проєктів щодо створення інноваційних продуктів. Інновації здатні підвищити конкурентоспроможність суб’єктів господарювання на ринку за рахунок удосконалення менеджменту на підприємствах, якісних маркетингових, кадрових та інноваційних політик.
Стратегічні напрями державного сприяння розвиткові підприємств в Україні: управлінські та фінансові аспекти
Keywords: strategic directions; state; development; стратегічні напрями; держава; розвиток; державне сприяння; підприємства; підприємництво